Identifikasi Potensi Air Tanah Menggunakan Metode Geolistrik di Dusun Krisik Desa Kemiri Kecamatan Jabung Kabupaten Malang - Nafi'atus Sholikhah; Vita Ayu Kusuma Dewi; Titi Rahayuningsih (G-Tech: Jurnal Teknologi Terapan, 2024)
Along with increasing human growth and activity, the need for clean water also continues to increase. Kemiri Village, Jabung Subdistrict, Malang often experiences clean water difficulties for daily needs, especially during the dry season. This study aims to determine the location of aquifers and potential groundwater discharge in Krisik Hamlet. The research method uses the Schlumberger Configuration Geoelectric Method and data analysis using IPI2WIN Software which is then smoothed using Progress 3 Software to identify aquifers and groundwater potential. Data acquisition was carried out on a 100-meter stretch of AB with 3 sounding points. Groundwater potential of the study area can be found at depths ranging from 0.04 - 44.71 meters bmt. The thickness of the aquifer layer ranges from 6.51 - 40.49 meters in the form of sandstone with resistivity values ranging from 164.69 - 248.84 Ωm. The type of aquifer found in the study area is unconfined aquifer in locations 1 and 2 and floating aquifer in location 3.